Peran CSR Dalam Mempengaruhi Pembelian Impulsif di Masa Pandemik - Andreas Wijaya; Anthony Japutra (Business Management Journal, 2021)
Data collection from world meters shows 6 months after announcement of the corona pandemic, several countries began to experience handling of corona cases which began to decline, however this was not the same as the results for several other countries, some countries showed cases that were increasing from day to day. data from the Central Statistics Agency (BPS) reported that the country's gross domestic product (GDP) in the second quarter of 2020 was minus to 5.32 percent. On a quarterly basis, the economy contracted 4.19 percent and cumulatively contracted 1.26 percent. Because of this, many companies are looking for ways to increase purchases. Scrutinized the data, the increase in the use of CSR has soared, proactively many companies have begun to engage in various CSR activities. One of the companies that are aggressively implementing CSR programs in helping others is online transportation providers; gojek. By providing the option of providing food to ojol partners (online motorcycle taxis) several options are offered to provide assistance. The sampling technique used in this study is to use a non-probability sampling method, which is a sampling technique that does not provide equal opportunities for each member of the population to selected to be the sample. Measurement of data in this study was carried out using a Likert scale. The development of this instrument contains a total of 16 attributes developed from each variable as a measurement basis for data collection with the sample used in this study being consumers who have the Gojek application. The data collected will be processed with SPSS software for data analysis in testing the validity, reliability, classical assumptions as verification of the strength of the research.